Skeletal myopathies as a non-cardiac cause of elevations of cardiac troponin concentrations - Giannitsis, Evangelos; Müller, Christian; Katus, Hugo (Diagnosis, 2019)
Abstract Skeletal myopathies have been suggested as a non-cardiac cause of elevations of cardiac troponin (cTn), particularly cardiac troponin T (cTnT). This is of major clinical relevance and concern as cTn plays a major role in the early diagnosis of myocardial infarction (MI). While both the incidence as well as the true pathophysiology (cardiac versus non-cardiac) underlying elevations in cTn in skeletal myopathies remain largely unknown, re-expression of cTnT in regenerating adult skeletal muscle has been suggested as a possible contributor. However, unequivocal protein characterization in skeletal muscle and quantification of the relative amounts of this possible signal versus the cTn signal derived from true cardiomyocyte injury remains elusive. Alternatively, minor cross-reactivity of the cTnT (and possibly at times also cTnI) detection and capture antibodies used in current monoclonal immunoassays with the skeletal troponin T or I isoform may be considered. Both would represent “false positive” elevations from a clinical perspective and would need to be reliably differentiated from “true positive elevations” from subclinical cardiomyocyte injury not detectable by currently available imaging techniques such as echocardiography and contrast enhanced magnetic resonance imaging (MRI), which have at least a 5 times lower sensitivity for cardiomyocyte injury. This review aims to explore the currently available data, its methodological limitations and provide guidance to clinicians to avoid misinterpretation of cTn concentrations.
Gesehen am 27.04.2020